The Government's Role in Facing SDGs 2030 Citarum River Clean-up Program, Indonesia: An Analysis - Fridayani, Helen Dian (Universitas Muhammadiyah Yogyakarta, 2020)
With a watershed area of 690,571, 57 hectares, Citarum is a source of agricultural irrigation water, hydroelectric power, and a source of raw water for drinking water as well as fishing and cultivation land that is utilized by residents in 10 districts and two cities in the province West Java. But Citarum today is faced with acute pollution which results in huge losses to health, economic, social, ecosystem, and environmental resources. This study will discuss how the government deals with SDGs 2030 by cleaning the Citarum River. In the future, it is normal that with government projects to clean up the waterway, the Citarum river is expected to be the cleanest river and can be used as much as possible. This study uses a literature review study with the focus of the study on how the government's role in solving the problem of water pollution in the Citarum river, then also focuses on how the government implements Citarum river cleaning programs. Government programs to clean up the Citarum river are considered good, but not yet optimal. Because until now there is still a recalcitrant industry that often dumps waste into the River Basin. Water pollution that occurs in the Citarum River ought to be of sure worry to the Indonesia government, particularly in West Java. By the several programs, neutral policies that protect the environment, and strict supervision it will be useful and works. Not only about the programs and policies that benefit the one-party but also other parties such as the environment and society.